Pain, disability and health-related quality of life in osteoarthritis—joint matters: an observational, multi-specialty trans-national follow-up study. Issue 9 (September 2016) - Montero, Antonio; Mulero, Juan-Francisco; Tornero, Carlos; Guitart, Jordi; Serrano, Mar
Abstract The authors aimed to test potential relations between osteoarthritis (OA) features, disability and health-related quality of life (HR-QoL) at different body locations. Outpatients consulting for pain associated to self-reported OA at varied healthcare settings were evaluated in a 3-month observational non-controlled follow-up study. Socio-demographic/anthropometric and medical data were collected at three time points. Lequesne's indices, quick-disabilities of arm, shoulder and hand (DASH) and Oswestry questionnaires provided measures of physical function and disability. HR-QoL measures were obtained with EuroQol-5 Dimensions. Multivariate analyses were used to evaluate the differences of pain severity across body regions and the correlates of disability and HR-QoL. Six thousand patients were evaluated. Pain lasted 2 years or more in 3995 patients. The mean pain severity at baseline was moderate (6.4 points). On average, patients had pain in 1.9 joints/areas. The pain was more severe when OA involved the spine or all body regions. Pain severity explained much of the variance in disability and HR-QoL; this association was less relevant in patients with OA in the upper limbs. There were considerable improvements at follow up. Pain severity improved as did disability, which showed particularly strong associations with HR-QoL improvements. Pain severity is associated with functional limitations, disability and poor HR-QoL in patients with self-reported OA. Functional limitations might have particular relevance when OA affects the upper limbs. Improvements are feasible in many patients who consult because of their pain.